2008
DOI: 10.1111/j.1398-9995.2007.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical asthma hazard of short‐acting β2‐agonists

Abstract: Paradoxical asthma hazard of short-acting b2-agonists Bonniaud et al. (1) report a case of bronchoconstriction in a patient caused by inhalation of short-acting b2-agonists. In an occupational setting, exposures to such agents can be even greater than those encountered therapeutically and there have been at least two reported cases of occupational asthma attributed to salbutamol exposure in pharmaceutical process workers (2). However, in the above-mentioned report the authors postulated that the mechanism mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…All short-acting β2 -adrenoceptor agonists approved by the FDA have warnings about causing paradoxical bronchospasm [4], and the instructions for terbutaline sulfate also suggest that the drug may cause bronchospasm, but the incidence rate the mechanisms are tillunknown. Some studies suggest that bronchospasm caused by β2 -adrenoceptor agonists may be mediated by IgE, and that salbutamol, terbutaline, and pibuterol share common structural features: a tert-butyl group attached to a nitrogen atom may explain that they can all bind to proteins to produce IgE and cause bronchospasm [11][12] . Other studies have suggested that β2 -adrenoceptor agonists induced bronchospasm may be related to inhalant excipients (propellants and surfactants), preservatives (benzalkonium bromide), osmotic pressure, and/or pH [1,8] .…”
Section: Discussionmentioning
confidence: 99%
“…All short-acting β2 -adrenoceptor agonists approved by the FDA have warnings about causing paradoxical bronchospasm [4], and the instructions for terbutaline sulfate also suggest that the drug may cause bronchospasm, but the incidence rate the mechanisms are tillunknown. Some studies suggest that bronchospasm caused by β2 -adrenoceptor agonists may be mediated by IgE, and that salbutamol, terbutaline, and pibuterol share common structural features: a tert-butyl group attached to a nitrogen atom may explain that they can all bind to proteins to produce IgE and cause bronchospasm [11][12] . Other studies have suggested that β2 -adrenoceptor agonists induced bronchospasm may be related to inhalant excipients (propellants and surfactants), preservatives (benzalkonium bromide), osmotic pressure, and/or pH [1,8] .…”
Section: Discussionmentioning
confidence: 99%
“…A review of adverse reaction reports for inhaled β 2 -selective, adrenergic-agonist bronchodilators between 1974 and 1988 revealed 126 reports consistent with a diagnosis of paradoxical bronchospasm associated with use of these drugs by metered-dose inhaler, and a further 58 such reports between 1983 and 1988 for these drugs delivered by nebulisation [13]. Salbutamol has been shown to cause occupational asthma in pharmaceutical workers and has an asthma hazard index of 0.84 on a scale of 0–1, with a value of 0.5 or higher indicating asthmagenic potential [14]. …”
Section: Discussionmentioning
confidence: 99%